Arna's Children - Khamis, Juliano Mer; Danniel, Danniel ((n/a), 2003)
coproduction: Israel, the Netherlands Documentary about a Jewish woman who set up a theater center for Palestinian children in a West Bank refugee camp, and some of her pupils who later became suicide bombers in the Israeli-Palestinian conflict. Contains amazingly candid views of warriors behind the scenes of battle.